Study on the Analytical Model of non-planar MOSFET - Munawar A. Riyadi; Darjat .; Teguh Prakoso; Jatmiko E. Suseno (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
In the recent development of MOSFET, non-planar structure has been identified as promising structure for next device generation. The advanced scaling of device implies that more sophisticated model is required due to the limitation of the existing models for application in nano scale. Analytical model for non-planar MOSFET model is discussed in this paper, especially for device with pillar. The concern of channel shape and structure is elaborated as well. The result shows the shift in subthreshold characteristic due to the presence of recessed region in the channel with the simulated model.